Developing and implementing a social prescribing initiative in primary care: insights into the possibility of normalisation and sustainability from a UK case study. Issue 2 (8th June 2016) - Whitelaw, Sandy; Thirlwall, Claire; Morrison, Amy; Osborne, Jill; Tattum, Lisa; Walker, Sharon
Abstract : Aim: To conduct a process-based evaluation of the inception and early implementation of a social prescribing initiative ( Healthy Connections Stewartry ) in two UK General Practices. Background: Prescribing a range of social, cultural, arts and educational activities to clients in primary care (known as 'social prescribing' or 'community linking schemes') as a means of addressing long-term physical health conditions and promoting mental health and well-being is becoming increasingly prominent and popular. However, concerns exist over a lack of evidence of effectiveness and formalised insights into how such initiatives may be optimally implemented. Methods: Within a case study design and using 1–1 semi-structured interviews, three related data sets were developed over a 12-month period from 30 purposively sampled informants: the project steering group; the wider primary care team; and various community groups. Data analysis drew on various theoretical resources, particularly those pertaining to nurturing sufficient capacity for the organisational 'normalisation' of this practice and understanding the dynamic flows and linkages between potential clients, 'prescribing' primary care staff and the available community resources. Findings: The inception and implementation of the initiative had been broadly successful and that more generally, there were grounds to suggest that these practices were becoming 'normalised' into the day-to-day cultures and routines of the primary care organisations. A series of procedural features are considered significant in achieving such ends. Some specific barriers to change are identified and ultimately in the context of potential 'transferability', a wider reflection is undertaken of the potential for such innovative practice to become established in less advantageous organisational circumstances. Fundamental difficulties are recognised and thus the need for formally implemented 'change' processes. Furthermore, for social prescribing to become a pervasive feature of health-care provision, the need for necessary capacity and resources is stressed.